2D photonic crystal layer assisted thiosilicate ceramic plate with red‐emitting film for high quality w‐LEDs. Issue 11 (5th July 2017) - Dai, Wubin; Lei, Yifeng; Zhou, Jia; Zhao, Yan; Zheng, Yunhao; Xu, Man; Wang, Shulin; Shen, Fan
Abstract: In this work, we have succeeded in obtaining high quality warm w ‐light‐emitting‐diodes (LEDs) by adopting hybrid two‐dimensional (2D) structure of SiN x photonic crystal layer (PCL) assisted cyan‐emitting ceramic‐plate thiosilicate SrLa2 Si2 S8 :Ce 3+ with red‐emitting film SrLiAl3 N4 :Eu 2+ phosphor on a 430 nm blue LED chip at 350 mA. 2D SiN x PCL was capped with thiosilicate is because it can enhance the luminous efficacy and maintain the low correlated color temperature (CCT) and high color‐rendering index (CRI). High luminous efficacy (82.3 lm/W), high special CRI (R9 =75) as well as the low CCT (5431 K) of the optimal w ‐LED was obtained due to the assistances of 2D SiN x PCL and narrow‐band red‐emitting phosphor with the doping percentage at 10 wt%. The synthesis processes, structural analysis, optical properties and LED device performances were detailed investigated to find out the relationship between the optimum composition and good optical properties. Based on intriguing luminescence properties by the 2D SiN x PCL and red‐emitting film phosphor introducing, we proclaim this method could also have high potential application in other phosphor‐converted w ‐LEDs.